(untitled) (INTERNATIONAL CONFERENCE ON MODERN DEVELOPMENT OF PEDAGOGY AND LINGUISTICS, 2026)
This article examines the poems of the national poet of Uzbekistan, Abdulla Oripov, which employ the art of antithesis to reflect a unique poetic meaning. Factors such as the emphasis placed on the contrast and the harmony of poetic image and content are analyzed. Based on the analysis and interpretation, certain scientific and theoretical conclusions are drawn.